The impact of organizational politics on work engagement—the mediating role of the doctrine of the mean - Su, Weijian; Xie, Chengxuan (Frontiers in Psychology, 2023)
The Affective Events Theory posits that the perception of organizational politics affects job attitudes. The purpose of this study was to answer the question: does organizational politics have a similar impact on Chinese individuals who adhere to the doctrine of the mean? To address this, we collected survey data from 3,059 library personnel in 36 Chinese university libraries. The results showed that the perception of organizational politics reduces employee work engagement. However, this impact exhibits heterogeneity. For newly recruited employees and employees aged 50 and above who are nearing retirement, the impact of organizational politics on work engagement is relatively small. Conversely, for employees aged 30 to 50, organizational politics has a significant negative impact. Furthermore, the doctrine of the mean moderates the impact of organizational politics on work engagement, mitigating its negative effects. The conclusions offer new insights into enhancing employee work motivation.